Sheikh Gentaru and the Traces of Cultural Islam in Kedungsari Tuwiri Wetan Merakurak Tuban - Ima Seftiyana Safira; Putri Nur Lailatun Nikmah; Nadia Salsabella Nur Fitria; Nurul Hakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines Syaikh Gentaru as a local Islamic scholar and his role in the development of cultural Islam in Kedungsari, Tuwiri Wetan Village, Merakurak District, Tuban Regency. Syaikh Gentaru is primarily known through oral traditions preserved by the local community, which portray him as a significant figure in the early process of Islamization at the local level, despite the limited availability of written historical records. Historically, he is believed to have lived during the period of Islamic expansion along the northern coast of Java, particularly during the era of the Demak Sultanate, when Tuban served as an important center of trade and Islamic propagation. Syaikh Gentaru employed a persuasive and culturally adaptive approach to da’wah, integrating Islamic teachings with existing local traditions without rejecting them entirely. This method facilitated a gradual and peaceful acceptance of Islam among the local population. Beyond his role as a religious preacher, he also functioned as a social leader and moral exemplar, contributing to the formation of both religious and social values within the community. The legacy of his cultural da’wah remains evident in contemporary society through practices such as grave pilgrimage, tahlilan, selametan, and haul commemorations, all of which represent a synthesis of Islamic teachings and local cultural expressions. Moreover, his influence is reflected in the community’s social life, which emphasizes values such as harmony, tolerance, and mutual cooperation. In conclusion, Syaikh Gentaru played a crucial role in shaping a model of cultural Islam that continues to be sustained and transmitted across generations in Kedungsari.